THE INFLUENCE OF GOOD CORPORATE GOVERNANCE, PROFITABILITY, LEVERAGE AND AUDIT QUALITY ON PROFIT MANAGEMENT IMPLEMENTATION (Study empirical on the company manufacture listed on IDX 2015 – 2019) - Rahayu; Agustin Fadjarenie; Lin Oktris, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
This study examines and presents models of the Influence of Good Corporate Governance , Profitability, Leverage and Audit Quality on the Implementation of Earnings Management in Manufacturing Companies Listed on the IDX for the 2015 – 2019 period. The purpose of this study is to determine the partial and simultaneous effect of variables Good Corporate Governance , Profitability, Leverage and Audit Quality on the implementation of earnings management in manufacturing companies listed on the IDX for the 2015-2019 period . The novelty of this study is the simultaneous influence of the four independent variables namely Good Corporate Governance , Profitability, Leverage and Audit Quality on the implementation of earnings management in manufacturing companies listed on the IDX for the 2015-2019 period. The type of research used is descriptive quantitative using multiple regression analysis as a technique for analyzing the research sample data. The results of this study are that there is a partial and simultaneous influence between the Good Corporate Governance , Profitability, Leverage and Audit Quality variables on the implementation of earnings management in manufacturing companies listed on the IDX for the 2015-2019 period.